Influence of the supramolecular arrangement of iron phthalocyanine thin films on catecholamine oxidation - Martin, Cibely S. [UNESP]; Alessio, Priscila [UNESP]; Crespilho, Frank N.; Brett, Christopher M.A.; Constantino, Carlos J.L. [UNESP] (Elsevier, 2019)
The versatility of iron phthalocyanine (FePc) to form distinct supramolecular arrangements in thin films, characterized by their thickness, molecular organization, morphology, and crystallinity, can be used to tune the electrochemical oxidation of catecholamines, becoming a promising material for sensing applications. Here, Langmuir-Schaefer (LS) and electrodeposition (ED) techniques have been used to produce thin films of FePc with different supramolecular arrangements on ITO electrodes. Both types of modified electrode were evaluated for the electrochemical oxidation of L-Dopa, dopamine (DA), norepinephrine (NEp), and epinephrine (Ep) in aqueous solution. The effect of scan rate, potential range, presence of oxygen, and pH were also evaluated, having an influence on the electrochemical oxidation of catecholamines. The FePc/ED modified electrodes showed two distinct peaks in the presence of mixtures of DA/L-Dopa and DA/Ep, while for FePc/LS modified electrodes an overlap of the oxidation waves was observed. This behaviour reveals the influence of the supramolecular arrangement of FePc on catecholamine oxidation. The FePc/LS modified electrodes showed a limit of detection of 0.024 μmol L −1 for DA and 0.168 μmol L −1 for L-Dopa, while FePc/ED showed limits of detection of 0.288 μmol L −1 and 0.564 μmol L −1 , respectively. The FePc films showed suitable properties for future application as catecholamine sensors.
Keywords: Catecholamines; Electrodeposition; Iron phthalocyanine; Langmuir-Schaefer